Pamięć, tabu, trauma w najnowszym kinie polskim: Przypadek Róży W. Smarzowskiego, Idy P. Pawlikowskiego i Pokłosia W. Pasikowskiego (Politeja, 2015)
Memory, Taboo, Trauma in Contemporary Polish CinemaContemporary film settlement of the twentieth‑century history, especially of experiences of World War II and Polish People’s Republic, on the one hand continues the tradition started by Polish Film School of de‑mythologizing trend, on the other hand – seeks new means of aesthetic expression. Through the analysis of Rose, dir. W. Smarzowski, Aftermath, dir. W. Pasikowski and Ida, dir. P. Pawlikowski, I present how the recent Polish cinema struggles with the collective trauma. As my research tools, I used concepts proposed by M. Hirsch, J.K. Olick, D. LaCapra and A. Landsberg, among others. That allowed me to take a look at relations between the protagonists inside diegesis, but also to reflect on the situation of the Polish cinema, which still struggles with, what M. Janion defined as “the post‑Romantic neurosis of Polish society”. However, I have tried to show, that “the politics of regret”, “the prosthetic memory” and, dictated by the logic of capitalism, the realities of postmemory in popular culture, may have also positive overtones in highlighting marginalised history.